Maximum size distributions in tropical forest communities: relationships with rainfall and disturbance - Poorter, L.; Hawthorne, W.; Bongers, F.; Sheil, Douglas (Wiley, 2008)
The diversity and structure of communities are partly determined by how species partition resource gradients. Plant size is an important indicator of species position along the vertical light gradient in the vegetation. Here, we compared the size distribution of tree species in 44 Ghanaian tropical forest communities, using data from 880 one‐hectare plots and over 118 000 trees belonging to more than 210 species. The size distribution of forest species showed a continuous normal or log‐normal distribution, with many canopy species and a few large species, and varied from community to community. Multiple regression showed that this variation is related to rainfall and to disturbance. Size distributions in wet forests were less skewed than those in dry forests, with a smaller proportion of big species and a smaller size range. At the same time they exhibited tighter species packing, resulting in higher species richness. Communities with high disturbance have less species packing and lower species richness. Synthesis. We conclude that the factors that constrain organism size and species coexistence in these tropical forest tree communities differ from those known to operate on a number of well‐studied animal communities.The diversity and structure of communities are partly determined by how species partition resource gradients. Plant size is an important indicator of species position along the vertical light gradient in the vegetation.Here, we compared the size distribution of tree species in 44 Ghanaian tropical forest communities, using data from 880 one‐hectare plots and over 118 000 trees belonging to more than 210 species.The size distribution of forest species showed a continuous normal or log‐normal distribution, with many canopy species and a few large species, and varied from community to community. Multiple regression showed that this variation is related to rainfall and to disturbance.Size distributions in wet forests were less skewed than those in dry forests, with a smaller proportion of big species and a smaller size range. At the same time they exhibited tighter species packing, resulting in higher species richness. Communities with high disturbance have less species packing and lower species richness.Synthesis. We conclude that the factors that constrain organism size and species coexistence in these tropical forest tree communities differ from those known to operate on a number of well‐studied animal communities.